Cool Control, Occam, and Océan: The Radigue and Bozzini Game - Majeau-Bettez, Emanuelle (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2017)
This article analyzes the dynamics of the new and current collaboration between the Montreal-based Bozzini String Quartet and female electronic music pioneer Éliane Radigue. Starting in the late 1960s, Radigue’s electronic music career has been characterized by seemingly unchanging hour-long pieces in which organic micro oscillations between pitches replace traditional rhythm. Since 2001, Radigue has turned to working with instrumentalists, using an “intuitive-instinctive compositional process” akin to “oral transmission of ancient traditional music” (Sonami 2017). While the few academics that have shown interest in Radigue’s instrumental music have focussed their attention on the oral aspects of her compositions, this paper seeks to move beyond non-written formal parameters of her music, and explore the ways in which the actual sound of a Radigue piece generates radically new understandings of performance and composition. Drawing on field notes and recordings of the Bozzini rehearsals at Radigue’s apartment on July 2017, as well as on the author’s correspondence with Radigue and the quartet, this paper highlights moments of strong emotional response to, or caused by, Radigue’s sound. Affective reactions on both Radigue’s and the quartet’s side reveal points of tension between different assumptions regarding collective creation, and completely reorient what it means to own, to transmit, to perform and to compose music. Spectrograms and recordings of the Bozzini’s attempts to create a Radigue sound will be used to further analyze these points of tension, and will reveal that in order to successfully play a Radigue instrumental piece, the Bozzinis need to reproduce every element of Radigue’s previous electronic music—the string quartet needs to “become” Radigue’s electronic instrument.